The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3390/diagnostics12122908
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Determination Using Pulse Co-Oximetry and Reduced-Volume Blood Gas Analysis in the Critically Ill: A Prospective Cohort Study

Abstract: Hospital-acquired anemia is common in patients hospitalized in the intensive care unit (ICU). A major source of iatrogenic blood loss in the ICU is the withdrawal of blood for laboratory testing. The aim of our study was to analyze the feasibility and accuracy of non-invasive spot-check pulse co-oximetry (SpHb), and a reduced-volume blood gas analysis (ABG Hb) for the determination of Hb concentration in critically ill patients. Comparisons between Hb determined with test devices and the gold standard—complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Non-invasive spectrophotometric hemoglobin measurement was only readable 151 of the 156 patients included in this study, because of the arrhythmia and low PI effe (failure rate of 3.20%). This failure percentage was similar to the 2% reported by Czem et al in their cohort study (2022) and the 5% in Frasca et al's prospective study (201 Both studies retrieved data from patients prior to surgery, as in our current study [28,2 Hornedo-González et al also reported no SpHb readings in 10 of the 122 patients in th study [30].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Non-invasive spectrophotometric hemoglobin measurement was only readable 151 of the 156 patients included in this study, because of the arrhythmia and low PI effe (failure rate of 3.20%). This failure percentage was similar to the 2% reported by Czem et al in their cohort study (2022) and the 5% in Frasca et al's prospective study (201 Both studies retrieved data from patients prior to surgery, as in our current study [28,2 Hornedo-González et al also reported no SpHb readings in 10 of the 122 patients in th study [30].…”
Section: Discussionsupporting
confidence: 90%
“…This failure percentage was similar to the 2% reported by Czempik et al in their cohort study (2022) and the 5% in Frasca et al's prospective study (2011). Both studies retrieved data from patients prior to surgery, as in our current study [28,29]. Hornedo-González et al also reported no SpHb readings in 10 of the 122 patients in their study [30].…”
Section: Discussionmentioning
confidence: 72%
“…It was possible to take non-invasive spectrophotometric hemoglobin measurements in 158 out of the 160 patients, and the recorded failure rate was only 1.25%. The failure rate was even higher in other studies conducted among patients with normal hemoglobin structure such as Czempik et al's cohort study (2022) (2%), Frasca et al's prospective study (2011) (5%), and Hornedo-González et al's study (8.19%) [34][35][36]. The current study is one of the few, if not the only one, to report the percentage of SpHb failure among patients with SCD.…”
Section: Failure To Measure Sphbmentioning
confidence: 50%
“…Factors that may impact device bias include: the sex of patients studied, with improved performance in male patients [ 19 ]; sex differences in perfusion index [ 19 ] with lower perfusion index in women [ 20 ]; and poorer device performance when hemoglobin is outside of the optimal level of device calibration [ 20 ]. The larger-than-expected biases observed in our study may be due to the female population with many anemic patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in anemic ICU patients concluded that non-invasive spot-check hemoglobin co-oximetry was not sufficiently accurate for clinical utility in their patient population [ 20 , 21 ]. Given the results of our study and the potential for clinical error as demonstrated on the hemoglobin error grid, we also conclude that SpHb is not sufficiently accurate for detecting anemia in postpartum patients.…”
Section: Discussionmentioning
confidence: 99%